ANALYSIS OF BUDURAN RIVER WATER QUALITY USING QUAL2KW AS RAW MATERIAL FOR SIWALANPANJI IPA - Wardhani, Putri Ayu; Mirwan, Mohammad (Directorate of Research and Community Service (DRPM), 2022)
Buduran River, Sidoarjo Regency, is one of the rivers in Sidoarjo City, which has various functions. The primary function of the Buduran River at the moment is to supply raw material water for one of the PDAM Delta Tirta Sidoarjo, namely the Drinking Water Treatment Plant (IPAM) branch in Siwalanpanji. For this reason, efforts are needed to maintain and monitor river quality using the Qual2Kw method. QUAL2Kw method begins with the determination of 3 segments. Furthermore, an analysis of hydraulic data, water quality, and pollutant sources was carried out, determining the scenarios used, running the QUAL2Kw program, and calculating the carrying capacity of pollution loads. River water quality parameters include pH, BOD, COD, TSS, Phosphate, and Nitrate. Applying the QUAL2Kw method in evaluating the Buduran River with three scenarios according to existing conditions, initial conditions according to quality standards, and trial & error with maximum pollutant load. The capacity value is determined based on the calculation of the difference in pollutant load in scenario three and scenario 2. The result is that the Buduran River is classified as a polluted river, and the negative (-) pollutant load capacity indicates that management is necessary to reduce pollutant loads.